ABNORMALITY IN THE RIGHT CHELA OF THE PORTUNID CRAB, PORTUNUS PELAGICUS LINNAEUS - Hamsa, K M S Ameer (Indian Journal of Fisheries, 2011)
An abnornial malfe crab .of Portunus pelagicus Linnaeus was obtained on9th June, 1971 from the giQ net (nandw vfl/